2010
DOI: 10.1063/1.3454918
|View full text |Cite
|
Sign up to set email alerts
|

Wide-range wavevector selectivity of magnon gases in Brillouin light scattering spectroscopy

Abstract: Brillouin light scattering spectroscopy is a powerful technique for the study of fast magnetization dynamics with both frequency and wavevector resolutions. Here, we report on a distinct improvement of this spectroscopic technique toward two-dimensional wide-range wavevector selectivity in a backward scattering geometry. Spin-wave wavevectors oriented perpendicularly to the bias magnetic field are investigated by tilting the sample within the magnet gap. Wavevectors which are oriented parallel to the applied m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 21 publications
0
50
0
Order By: Relevance
“…These measurements were performed using a rotating sample stage as described in ref. 31 with a wavenumber resolution DqD0.4 Â 10 4 cm À 1 . In the case of a low pumping power of 1 W-corresponding to the case of a moderate heating of the magnon gas-a clear concentration of magnons occurs at the global energy minimum (compare Figs 4a and 6a) q ¼ 4 Â 10 4 cm À 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These measurements were performed using a rotating sample stage as described in ref. 31 with a wavenumber resolution DqD0.4 Â 10 4 cm À 1 . In the case of a low pumping power of 1 W-corresponding to the case of a moderate heating of the magnon gas-a clear concentration of magnons occurs at the global energy minimum (compare Figs 4a and 6a) q ¼ 4 Â 10 4 cm À 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to geometrical constraints of the rotating stage, the magnons are detected up to q ¼ 1.1 Â 10 5 cm À 1 with wavenumber resolution of DqC0.4 Â 10 4 cm À 1 (ref. 31). The frequency resolution of our BLS measurements is 150 MHz.…”
Section: Methodsmentioning
confidence: 99%
“…A particularly well characterized magnet is yttrium-iron garnet (YIG) 21 . The momentum distribution function of the magnon gas in YIG has been probed experimentally using the technique of Brillouin light scattering 6,22,23,39 . At long wavelengths the energy dispersion of the experimentally relevant magnon band in thin YIG-stripes can be approximated by Eq.…”
Section: Thermalization Of Magnons In Yigmentioning
confidence: 99%
“…1,2 By exploiting this property, along with number-conserving internal scattering processes, it is reported that Bose-Einstein condensation (BEC) of magnons can be achieved in YIG films with thicknesses of a few microns. 3 Brillouin light scattering, 4,5 which was used in the BEC experiments, has proven to be a powerful tool to characterize short wavelength spin waves launched from stripline antennas and, more broadly, their distribution under thermal equilibrium and non-equilibrium conditions. But if devices based on short wavelength magnons are to emerge, it is anticipated that techniques to strongly couple to directed spin waves in a wavelength-specific manner will be required, and towards this end we are experimenting with multi-element antennas to generate and detect such waves.…”
Section: Introductionmentioning
confidence: 99%